Determinants and Consequences of Obesity - Hruby, Adela; Manson, JoAnn E.; Qi, Lu; Malik, Vasanti S.; Rimm, Eric B.; Sun, Qi; Willett, Walter C.; Hu, Frank B. (American journal of public health (1971), 2016)
Objectives. To review the contribution of the Nurses’ Health Studies (NHS and NHS II) in addressing hypotheses regarding risk factors for and consequences of obesity. Methods. Narrative review of the publications of the NHS and NHS II between 1976 and 2016. Results. Long-term NHS research has shown that weight gain and being overweight or obese are important risk factors for type 2 diabetes, cardiovascular diseases, certain types of cancers, and premature death. The cohorts have elucidated the role of dietary and lifestyle factors in obesity, especially sugar-sweetened beverages, poor diet quality, physical inactivity, prolonged screen time, short sleep duration or shift work, and built environment characteristics. Genome-wide association and gene–lifestyle interaction studies have shown that genetic factors predispose individuals to obesity but that such susceptibility can be attenuated by healthy lifestyle choices. This research has contributed to evolving clinical and public health guidelines on the importance of limiting weight gain through healthy dietary and lifestyle behaviors. Conclusions. The NHS cohorts have contributed to our understanding of the risk factors for and consequences of obesity and made a lasting impact on clinical and public health guidelines on obesity prevention.